Student motorcyclists' mobile phone use while driving in Vientiane, Laos. Issue 2 (3rd April 2017) - Phommachanh, Sysavanh; Ichikawa, Masao; Nakahara, Shinji; Mayxay, Mayfong; Kimura, Akio
Abstract : To investigate mobile phone use while driving among student motorcyclists in Laos, we conducted a school-based questionnaire survey in central Vientiane in May 2014. Of the 883 high school students who reported to drive motorcycles at least once a week, 40% have ever used phones while driving motorcycles in both sexes. Those phone users had longer driving exposures than non-users, with about half engaging in phone use while driving at least 2 days a week and 70% engaging for 1 min or longer on an average day. They reported not just talking on the phone while driving but operating the phone such as dialling and text-messaging. In some instances, phone use was reportedly involved in their past crash experiences. To formulate a sound policy on this emerging distracting behaviour among motorcyclists, its contribution to the occurrence of overall crashes among motorcyclists should be investigated.